A. PENERAPAN SEGITIGA RESTITUSI DALAM MENINGKATKAN AKSI NYATA DISIPLIN POSITIF PESERTA DIDIK PADA MATA PELAJARAN SENI BUDAYA KELAS XI DI SMAN 1 LOHBENER: PENERAPAN SEGITIGA RESTITUSI DALAM MENINGKATKAN AKSI NYATA DISIPLIN POSITIF PESERTA DIDIK PADA MATA PELAJARAN SENI BUDAYA KELAS XI DI SMAN 1 LOHBENER - Agus Fidyani; Moh. Ali; Dewi Cahyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The restitution triangle approach that emphasizes reflection, admission of mistakes, and self-improvement is considered effective in improving discipline without relying on punishment or rewards. Although SMAN 1 Lohbener has implemented positive discipline, there are still violations of rules by students. This study aims to describe the implementation of the restitution triangle in improving positive discipline of students in the arts and culture subject of grade XI at SMAN 1 Lohbener. This study is a qualitative study with a case study method using strategies to solve problems with the restitution triangle action, especially on issues of disciplinary violations such as attendance, punctuality, honesty, obeying established class agreements, and consciously and openly admitting when making mistakes. Data collection was carried out using observation, interview, documentation, and questionnaire methods. Data analysis used the Miles and Huberman model which focuses more on three main components, namely data reduction, data presentation, and conclusion drawing. The results of the study showed that the restitution triangle succeeded in increasing positive discipline. The implementation of positive discipline in question includes the stages of implementation carried out technically and the application of positive discipline in essence, namely the application of 7 principles of positive discipline. The results showed that the implementation of positive discipline was carried out through 3 stages, namely the socialization stage, the preparation stage, and the implementation stage. The object of this study was class XI with a total of 43 students, the process was carried out from September to November, the results obtained increased student discipline from 65% to 86%. Thus, the restitution triangle applied in the classroom was able to increase student discipline.